Comparison of cytomegalovirus-specific immune cell response to proteins versus peptides using an IFN-γ ELISpot assay after hematopoietic stem cell transplantation - Wagner-Drouet, Eva; Teschner, Daniel; Wolschke, Christine; Schäfer-Eckart, Kerstin; Gärtner, Johannes; Mielke, Stephan; Schreder, Martin; Kobbe, Guido; Hilgendorf, Inken; Klein, Stefan; Verbeek, Mareike; Ditschkowski, Markus; et al. (Diagnostics, 2021)
Cytomegalovirus (CMV) infection is a major cause of morbidity and mortality following hematopoietic stem cell transplantation (HSCT). Measuring CMV-specific cellular immunity may improve the risk stratification and management of patients. IFN-γ ELISpot assays, based on the stimulation of peripheral blood mononuclear cells with CMV pp65 and IE-1 proteins or peptides, have been validated in clinical settings. However, it remains unclear to which extend the T-cell response to synthetic peptides reflect that mediated by full-length proteins processed by antigen-presenting cells. We compared the stimulating ability of pp65 and IE-1 proteins and corresponding overlapping peptides in 16 HSCT recipients using a standardized IFN-γ ELISpot assay. Paired qualitative test results showed an overall 74.4% concordance. Discordant results were mainly due to low-response tests, with one exception. One patient with early CMV reactivation and graft-versus-host disease, sustained CMV DNAemia and high CD8+ counts showed successive negative protein-based ELISpot results but a high and sustained response to IE-1 peptides. Our results suggest that the response to exogenous proteins, which involves their uptake and processing by antigen-presenting cells, more closely reflects the physiological response to CMV infection, while the response to exogenous peptides may lead to artificial in vitro T-cell responses, especially in strongly immunosuppressed patients.
Gesehen am 07.07.2021